87.2k views
1 vote
Perform the multiplication, (7x2+a2)(x2–3a2)

1 Answer

5 votes

Answer:

The given multiplied expression is


(7x^2+a^2)(x^2-3a^2)=7x^4-20x^2a^2-3a^4

Explanation:

Given expression is
(7x^2+a^2)(x^2-3a^2)

To find the multiplication of the given expression :


(7x^2+a^2)(x^2-3a^2)

By using the distributive property to solve the given expression as below


(7x^2+a^2)(x^2-3a^2)=(7x^2)(x^2)+(7x^2)(-3a^2)+(a^2)(x^2)+(a^2)(-3a^2)


=7x^2.x^2-21x^2a^2+a^2x^2-3a^2.a^2


=7x^(2+2)-21x^2a^2+a^2x^2-3a^(2+2) ( by using the property
a^m.a^n=a^(m+n) )


=7x^4-21x^2a^2+a^2x^2-3a^4

Adding the like terms in the above expression we get


=7x^4-20x^2a^2-3a^4

Therefore
(7x^2+a^2)(x^2-3a^2)=7x^4-20x^2a^2-3a^4

Therefore the given multiplied expression is


(7x^2+a^2)(x^2-3a^2)=7x^4-20x^2a^2-3a^4

User Snarik
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.